2015
DOI: 10.1371/journal.pone.0128069
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Extension of Pegylated Interferon Alpha and Ribavirin Does Not Improve SVR in Patients with Genotypes 2/3 without Rapid Virological Response (OPTEX Trial): A Prospective, Randomized, Two-Arm, Multicentre Phase IV Clinical Trial

Abstract: Although sofosbuvir has been approved for patients with genotypes 2/3 (G2/3), many parts of the world still consider pegylated Interferon alpha (P) and ribavirin (R) as standard of care for G2/3. Patients with rapid virological response (RVR) show response rates >80%. However, SVR (sustained virological response) in non-RVR patients is not satisfactory. Longer treatment duration may be required but evidence from prospective trials are lacking. A total of 1006 chronic HCV genotype 2/3 patients treated with P/R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 24 publications
0
12
1
Order By: Relevance
“…SVR12 rates in this real world GECCO cohort were lower compared to phase III trials with comparable DAA regimes but much higher than those rates reported in the era of dual PEG/RBV‐based therapy in other real world cohorts …”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…SVR12 rates in this real world GECCO cohort were lower compared to phase III trials with comparable DAA regimes but much higher than those rates reported in the era of dual PEG/RBV‐based therapy in other real world cohorts …”
Section: Discussioncontrasting
confidence: 60%
“…SVR12 rates in this real world GECCO cohort were lower compared to phase III trials with comparable DAA regimes but much higher than those rates reported in the era of dual PEG/RBV-based therapy in other real world cohorts. 17,18 SVR12 rates in non-cirrhotic patients who received a 12 week course of SOF/DCV ± RBV were higher as compared to SOF/RBV patients and only slightly lower as reported in the ALLY-3 trial. 13 Importantly, 12 weeks of SOF/DCV ± RBV were equally effective in treatment-experienced and −naïve patients, as reported before.…”
Section: Discussionmentioning
confidence: 65%
“…In this study, transient elastography (TE, Fibroscan ® ; Echosens, Paris, France) and Acoustic Radiation Force Impulse (ARFI) (Siemens Acuson S2000, Munich, Germany) elastography were used for assessment of liver fibrosis . In case of incongruent results in ARFI and TE or in cases of missing values of both, platelet counts, the AST/ALT ratio and the concentration of bilirubin and albumin were determined …”
Section: Methodsmentioning
confidence: 99%
“…21,22 In case of incongruent results in ARFI and TE or in cases of missing values of both, platelet counts, the AST/ALT ratio and the concentration of bilirubin and albumin were determined. 23 Measurements of ARFI and TE were performed at the same day after an overnight fast. For ARFI, only procedures with at least 10 valid acquisitions and a success rate of at least 60% were defined as eligible for the study.…”
Section: Definition Of Cirrhosismentioning
confidence: 99%
“…High rates of SVR12 were achieved even in patients, who were generally considered "difficult-totreat", such as patients with cirrhosis or those previously treated, and in HIV co-infected patients. Moreover, SVR12 rates in the real world GECCO cohort were lower compared to phase III trials with comparable DAA regimes, yet were much higher than rates reported in the era of dual PEG/RBV-based therapy real world cohorts (18)(19)(20).…”
Section: Sof + Rbv Ldv/sof +/-Rbv Sof/dcl +/-Rbv Sof/vel +/-Rbv Omv/pmentioning
confidence: 73%